Loss of Heterozygosity Analysis Using Whole Genome Amplification, Cell Sorting, and Fluorescence-Based PCR - Paulson, Thomas G. (Cold Spring Harbor Laboratory Press, 1999)
Loss of heterozygosity (LOH) is a common genetic lesion found in many human neoplasms. Extending investigation of LOH to large-scale clinical and public health science studies has proven difficult because of the small size and cellular and genetic heterogeneity of human neoplasms, in addition to the challenges associated with increasing throughput. Our approach to LOH analysis was developed using clinical biopsy samples from patients with Barrett’s esophagus (BE) and uses flow cytometric cell sorting to increase sample purity, whole genome amplification to increase sample amount, and automated fluorescent genotyping to increase sample throughput. This approach allows LOH assessment at 20 loci in DNA extracted from 1000 flow-purified cells while maintaining accurate and reproducible allele ratios compared with the standard method of using genomic DNA. This method of analysis should allow accurate, reproducible determination of allele ratios in a variety of human tumors and premalignant conditions.